KOMUNIKASI INTERPESONAL ORANG TUA DAN ANAK DALAM MENGATASI PERNIKAHAN USIA DINI DI NAGORI LINGGA KABUPATEN SIMALUNGUN - Adelia Syavitri; Anang Anas Azhar; Fakhrur Rozi (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The title of this research is "Interpersonal Communication of Parents and Children in Overcoming Early Marriage in Nagori Lingga, Simalungun Regency". This study aims to determine the causes of early marriage in Nagori Lingga and to find out how Interpersonal Communication between parents and children in overcoming early marriage. The theory used in this research is the Accommodation theory. This research was conducted using Descriptive Qualitative methods. By obtaining the results of the study, namely, that the cause of early marriage in Nagori Lingga, Simalungun Regency, is because one of the factors is that most of them are already pregnant first, besides that there are also the wishes of their children because they are no longer in school, promiscuity, education that is still very low to continue higher schooling and inadequate economic factors. Parents take it for granted when their children choose to marry at an early age, some feel sad and moved because they are still young to be married and make a disgrace in the family, namely pregnant first (pregnant outside of marriage). In early marriage, it is the parents who must be the mediator in their children's households, because we know what children who marry at a young age are like, if in terms of their emotions cannot be controlled, and their thinking is still very unstable, they are more prone to quarreling, and misunderstanding, therefore their job as parents is to advise their children, give understanding, always give direction to their children.